Hubungan antara Konsep Diri, Kepercayaan Diri dengan Kemampuan Komunikasi Interpersonal dalam Proses Pembelajaran pada Mahasiswa - M. Reza Kurniawan; Ernita Arif; Asmawi Asmawi (Mahesa Research Center, 2021)
to 2020, a sample of 160 people was obtained. The results of the validity test obtained 8 invalid items. Based on the research results obtained from respondents the self-concept is classified as very good, the respondent's self-confidence is good and then the respondent's interpersonal communication skills are classified as good. Based on the results of the study, it is concluded that self-concept has a significant influence on interpersonal communication skills in the learning process for students of the Faculty of Economics and Islamic Business, Imam Bonjol University, Padang, so the first hypothesis is accepted, self-confidence has a significant influence on the interpersonal communication skills of the learning process in students, then The second hypothesis is accepted and self-concept and self-confidence variables simultaneously have a significant influence on interpersonal communication skills in the learning process for students of the Faculty of Economics and Islamic Business, Imam Bonjol University, Padang.